Associations between weekend catch-up sleep and health-related quality of life with focusing on gender differences - Jinkyung Oh; Eunmi Kim; Iksoo Huh (Scientific Reports, 2023)
Abstract This study investigated associations between weekend catch-up sleep (WCUS) and health-related quality of life (HRQoL) in 15,837 participants from the 7th (2016–2018) Korea National Health and Nutrition Examination Survey. We categorized WCUS durations into four groups: none (≤ 0 h [h]), short (> 0 h, ≤ 1 h), medium (> 1 h, ≤ 2 h), and long (> 2 h), and performed complex samples logistic regression and likelihood ratio χ2 test. The study found significant associations in women for the European Quality of Life-5 Dimensions (EQ-5D) index and three EQ-5D subdomains (self-care, usual activities, and anxiety/depression) with the WCUS durations, but no significant association in men. Compared to the non-WCUS, the short or medium WCUS was positively associated with the EQ-5D index and EQ-5D subdomains (usual activities and anxiety/depression) in women, while the long WCUS significantly reduced the quality of life in the self-care domain. In an additional subgroup analysis by age, middle-aged and elderly women had a more noticeable effect of WCUS on HRQoL than young women, and the short or medium WCUS improved HRQoL in middle-aged and elderly women in general. Therefore, we recommend appropriate WCUS durations to improve HRQoL, considering both gender and age.